Testes diagnósticos para detecção de bovinos infectados por Mycobacterium bovis - Vidal, Carlos Eugênio Soto (2013)
Bovine tuberculosis remains a global health problem, both for developing countries, as for the developed countries. The presence of the bacterium Mycobacterium bovis represents a hazard to human and cattle population and its detection depends on diagnostic tools, which are still imperfect. This thesis describes part of the problem of the performance evaluation of two indirect enzyme-linked immunosorbent assays (ELISAs), one in experimental stage and the other a commercial kit to detect antibody of cattle naturally infected by M. bovis, when other diagnostic techniques also fail to hit the result. We also show the problem faced by the threshold of the cervical comparative tuberculin (CCT) test, which is the method most widely used for the control and eradication of bovine tuberculosis in field use. Twenty-one herds of cattle, 19 of dairy production and two predominantly for beef production, have been tested with the CCT and the ELISAs’ results have been compared, using 2703 serum samples collected simultaneously. The experimental ELISA uses a chimera formed of three proteins fragments of M. bovis, MPB-70, MPB-83 and ESAT-6 as antigen, and the commercial ELISA uses the MPB-70 and MPB-83. The experimental ELISA detected all 10 CCT positive herds and the commercial ELISA has detect nine of them. The experimental ELISA also detected more cattle as positive. In the second article, the CCT, which is the reference test for bovine tuberculosis control, was analyzed in a herd, when the skin-fold increase produced false-negative, in detriment of the decision making when the cut-off point is taken to the letter. The false-negative results must be considered both in controlling the disease in farms infected by M. bovis, as in surveillance studies using this test.